(3OjhGf GdeTYTYjs - (3Ydj Hf Nda Hf YHO GdeWdH Hf MjOQ Hf eMeO Hf adGM GdehShj GdMhjRj GdeTYTYj,J (B1087 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efg(B: (3GdOgQ MQH GdYdhi de jRd hGdaGVd GdMHQ, hSde GdLGgd s
(3BNQgG (B:s
(3eHJhQ CjVkG hBNQ GdehLhO efg(B: (3hdh bjd dj(B: (3eGPG JQjO ef Gdefi dcGf oefGj hGdEQGOI CfJe s
(3GdeDda cGf MjkG SfI (B1087(3g````s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B208 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs